Illustration and the Influence of Illustrator on Children’s Understanding of Fairy Tales and Works of Art in Books - Sarvar Tursunmurotovich, Sobirov; Xayitboy Eraliyevich, Sultanov; Ulfat Shuhratovich, Ismatov (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the features of children’s perception of the text in fiction books and fairy tales. It also discusses children’s art books and fairy tales, as well as the artist’s influence on illustrations and illustrators for fairy tales and fiction books, book graphics, and graphic artists’ understanding of the text in fairy tales.